Islamic tarbiyah in contemporary higher learning institution in Malaysia:The case of the International Islamic University Malaysia - Md. Noon, Hazizan (2016)
This paper elucidates the translation into practice of Islamic educational ideals, as rooted in and derived from the very source of Islamic religion namely the Divine revelation, at a higher learning institution in Malaysia namely the International Islamic University Malaysia (IIUM). It has two parts: the theoretical and the applied. Part I deals with the conceptual issues focussing mainly on the ideological basis of Islamic tarbiyah including discussion of the Islamic concept of knowledge which is closely related to the philosophy of Islamic education. Part 2 addresses the application of this Islamic educational philosophy into practice with particular reference to the experiment, experience and model of IIUM. The former provides preliminary background for discussion of the latter which is the focus of this paper. Special attention is given to elaborating the curricular activities conducted by the University in its efforts to develop and enhance the wholesome character of its students, which is regarded as the essence of Islamic education.